The development of chaos theory and the human factor within interdisciplines - Salamanca - Ladino, Nahir Saraí; Triana - Castrillo, Ángela Daiyan; Vega - Cantero, Juliana Carolina; Guevara - Triana, Laura Alejandra; Sinisterra - Lozano, Nara Xamanta (Universidad Francisco de Paula Santander, 2022)
The chaos theory out of the mind of Edward Lorenz by mistake, leads to propose a series of elements which have intervened in the different disciplines and which they have included in their fields of action, thus marking a transversal line that allows observing the progress of it is in front of any branch of any science becoming opportune for humanity. Demonstrating that the human factor intervenes to modify a planning within an organized group, evidencing the variability of options or directions that an organization can carry out, in which the trajectory is modified by the decisions made by the leaders or by the change that It has the initial act, having for this good or bad repercussions, showing that the exactions are not true at least in the organizational management (disciplines) and that everything is carried out by means of predictions or beliefs. Chaos theory is ultimately a determining factor in the development of organized business systems, highlighting their initiative and creativity in the face of changing circumstances.